Distribution of harmful gas and ventilation length design of high altitude long gas tunnel construction: a case study - Zhang, Xueqiang; Hu, Juyi; Zhang, Danfeng; Cai, Shuang; Yang, Feng (Frontiers in Earth Science, 2023)
The air density in high altitude gas tunnel is small and the air supply is difficult. The jet tunnel ventilation is a common construction ventilation mode. In order to explore the pollutant distribution characteristics and the optimal ventilation length of tunnel ventilation in high altitude gas tunnel, Ningchan tunnel has been taken as the engineering background, the fluid dynamics software FLUENT has been used to establish a three-dimensional model of jet tunnel ventilation, the distribution characteristics of methane, hydrogen sulfide and other harmful gas in the tunnel have been studied, and the optimal ventilation length of tunnel ventilation in high altitude gas tunnel degree has been explored. The results show that: the minimum ventilation length required in the existing technical specifications of gas tunnel is not reasonable, which leads to the existence of low-speed wind area in the tunnel, and harmful gas is easy to gather in the single head section, and the gas concentration can reach 0.59% at 2 m away from the working face; by reducing the ventilation length, the gas concentration in the single head section can be effectively reduced, and when the ventilation length is 1200 m, the gas concentration at 2 m away from the working face will be reduced to 0.31%; setting local fan in front of the roadway can also significantly improve the accumulation degree of harmful gas in the single end section. The maximum gas concentration of working face reduced to 0.24%, and the average gas concentration of reduced to 0.15%. The results can provide reference for ventilation scheme of high altitude gas tunnel construction.